2010
DOI: 10.1007/s00296-010-1369-6
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise in fibromyalgia: a practical review

Abstract: The objective of the study was to determine the current evidence to support guidelines for aerobic exercise (AE) and Wbromyalgia (FM) in practice, and to outline speciWc research needs in these areas. Data sources consisted of a PubMed search, 2007 Cochrane Data Base Systematic review, 2008 Ottawa panel evidence-based clinical practice guidelines, as well as additional references found from the initial search. Study selection included randomized clinical trials that compared an aerobic-only exercise interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 34 publications
2
48
0
3
Order By: Relevance
“…Sabe-se que o exercício físico é crucial como parte do tratamento destes pacientes e evidências recentes mostram benefícios moderados dos exercícios físicos, sobretudo os aeróbicos, na capacidade funcional e possivelmente na dor 28 . Apesar destes achados na literatura, é difícil afirmar que o NAF, no presente estudo, pôde ter influenciado nas associações entre dor e capacidade funcional.…”
Section: Discussionunclassified
“…Sabe-se que o exercício físico é crucial como parte do tratamento destes pacientes e evidências recentes mostram benefícios moderados dos exercícios físicos, sobretudo os aeróbicos, na capacidade funcional e possivelmente na dor 28 . Apesar destes achados na literatura, é difícil afirmar que o NAF, no presente estudo, pôde ter influenciado nas associações entre dor e capacidade funcional.…”
Section: Discussionunclassified
“…Most studies examining the effects of aquatic exercise have therefore focused on adults with problems such as osteoporosis, ankylosing spondylitis, spinal cord injury, or fibromyalgia syndrome [24][25][26][27][28]. However, the few studies that have measured sleep outcomes from aquatic exercise suggest that it may produce greater benefits for sleep than land-based exercise [29][30][31][32][33] and therefore has potential benefits for older adults facing sleep difficulties. Studies are therefore needed to assess the effectiveness of aquatic exercise specifically designed to improve sleep quality among older adults who have poor sleep quality.…”
Section: Introductionmentioning
confidence: 99%
“…1 2 Fibromyalgia is becoming a common syndrome in Western European countries, and estimates indicate a point prevalence of 2.9%, which translates to approximately six million people with fibromyalgia. 3 There is increasing evidence about the potential benefits of regular physical activity on fibromyalgia-related symptoms, [4][5][6][7] and international organisations support the use of physical activity-based interventions as a complementary tool in the therapeutic armamentarium against fibromyalgia. 8 Physical inactivity is one of the major public health problems of the 21st century, 9 and several longitudinal studies have shown the negative consequences on health through a sedentary lifestyle.…”
Section: Introductionmentioning
confidence: 99%